Individual differences in the activity of the hypothalamic pituitary adrenal axis: Relations to age and cumulative risk in early childhood. (July 2017) - Holochwost, Steven J.; Gariépy, Jean-Louis; Mills-Koonce, W. Roger; Propper, Cathi B.; Kolacz, Jacek; Granger, Douglas A.
Highlights: We assess the bioavailability and toxicity of Au-ZnO NPs in the clams Ruditapes decussatus Au-ZnO NPs exposure causes accumulation and deregulation of transitional metals Exposure to Au-ZnO NPs causes an increase in H2O2 level, SOD and CAT activities and MDA content Au-ZnO NPs exposure disrupts histological structure in both tissues Abstract: This study examined individual differences in the function of the hypothalamic-pituitary-adrenal (HPA) axis with regard to age and cumulative risk during challenging laboratory tasks administered at 6, 12, 24, and 36 months. Saliva samples were collected from a majority-minority sample of N = 185 children (57% African American, 50% female) prior to and following these tasks and later assayed for cortisol. Cumulative distal risk was indexed via a composite of maternal marital status, maternal education, income-to-needs ratio, the number of children in the household, and maternal age at childbirth. Probing of hierarchical models in which cortisol levels and age were nested within child revealed significant differences in cortisol as a function of both age and cumulative risk, such that children exposed to high levels of risk exhibited higher levels of cortisol both within and across age. These results highlight the sensitivity of the HPA axis to environmental context at the level of the individual, even as that sensitivity is manifest against the background of species-typical biological development.